(Sr1-xCax)2SnO4 microwave dielectric ceramics with Ruddlesden-Popper structure (x = 0–0.06) for microwave application - Raj Kumar; Vipin Kumar Gupta; Upendra Kumar (Next Materials)
In this study, (Sr1-xCax)2SnO4 (0 ≤ x ≤ 0.06) ceramics were synthesized via a conventional solid-state reaction method to investigate the effect of Ca2 + substitution on their structural and microwave dielectric properties. Rietveld refinement study confirmed the formation of a single-phase tetragonal Ruddlesden–Popper (R–P) structure with space group I4/mmm across all compositions. The progressive replacement of larger Sr²⁺ ions with smaller Ca²⁺ ions at the A-site led to a systematic reduction in lattice parameters, indicating successful ionic substitution and lattice distortion. Vibrational analyses using Fourier transform infrared and Raman spectroscopy validated the R–P phase, with characteristic Sn–O stretching bands at 582 cm−1 and 726 cm−1, and a prominent Raman peak at 570 cm−1. Microwave dielectric measurements revealed that the relative permittivity (εᵣ) and the quality factor (Q×f) increased with Ca content up to x = 0.02, due to improved microstructural densification and reduced defect-induced dielectric losses. Additionally, the temperature coefficient of resonant frequency (τf) decreased with increasing Ca content, reaching a minimum of 1.45 ppm/°C at x = 0.02, suggesting enhanced thermal stability attributed to modified bond dynamics and increased lattice rigidity. The optimal composition (x = 0.02) demonstrated excellent dielectric performance, with εᵣ = 33, Q×f = 32,517 GHz, and near-zero (τf), making it a promising candidate for high-performance microwave dielectric applications in next-generation telecommunication systems.